MONITORING OF LOCUST SPECIES THAT CAUSE CROWDS OF HARVEST IN UZBEKISTAN - Shоmurоdov Sherzod Chori ugli; Khalmuminova Gulchehra Kulmuminovna; Boboqulov Ogabek Abdikodir ugli (Galaxy International Interdisciplinary Research Journal, 2023)
Providing the population with food products in our republic is included in the state program. is one of the most urgent tasks of today. One of the main reasons for the increase of harmful locusts in various regions of our republic and in some cases they fly to agricultural crops is the increase in the number of livestock in the existing pastures, the expansion of the area of agricultural crops, and the historical foci of locusts. due to the establishment of vegetable, sugarcane crops and intensive orchards in nearby fields, harmful locusts are causing migration to agricultural crops. Despite the fact that the fight against harmful locusts in our republic is carried out in their historically widespread foci, in some cases, they move to newly established intensive gardens and other agricultural crops and cause damage.